Tooth loss in treated periodontitis patients responsible for their supportive care arrangements - W. K. Leung (journal of clinical periodontology, 2006)
Aim: To identify risk indicators associated with tooth loss and periodontitis in treated patients responsible for arranging supportive periodontal care (SPC). Materials and Methods: Ninety-seven Chinese subjects (34–77 years) who showed favourable responses to periodontal therapy provided in a teaching hospital 5–12 years previously were recalled. They were advised to seek regular SPC on discharge. Background information, general health status, smoking, oral hygiene habits, followup dental care, tooth loss, and periodontal parameters were investigated. Multiple regression analysis was performed. Results: Two hundred and fifty-six teeth had been lost, 195 because of self-reported periodontal reasons. Up to 26.8% sites were with pockets X6 mm. Positive correlations were found between total/periodontal tooth loss and (i) smoking packyears, (ii) time spent on oral hygiene, (iii) years since therapy’s conclusion, (iv) age, and negative correlations with (v) inter-dental brush use, and (vi) education levels. Tooth loss by arch was correlated with wearing of removable partial denture in that arch. Percentage sites with pockets X6mm were significantly negatively correlated with percentage sites without bleeding on probing. Conclusions: Smokers, more elderly patients, removable partial denture wearers, and patients with lower education levels or not using inter-dental brushes ought to be targeted for clinic-based SPC.